Submit in any of the following roles if you would like to be able to edit and publish this submission yourself: Journal manager - Santoso, Budi Imam; Hardati, Puji; Suharini, Erni (Jurusan Geografi, Fakultas Ilmu Sosial, Universitas Negeri Semarang, 2019)
Facilities and infrastructure are limited, the lack of jobs in Lebo Village causes residents to mobility to other areas. The purpose of this study is to determine the factors that cause residents to do mobility. This study uses a quantitative approach. The population of this study were all households in Lebo Village, which amounted to 1209 households. The sampling method uses Proposiate Area Random Sampling of 10% of the population and produced 120 households. Data collection techniques used are questionnaires, observation and documentation. The data analysis technique uses descriptive percentage (DP). The variables of this study are the driving and pulling factors that cause the population to do mobility.The results of this study indicate factors from Desa Lebo such as the lack of facilities and infrastructure, employment, low employment wages which caused residents to do mobility to other regions. Attractive factors from other areas such as more complete facilities and infrastructure, many jobs, higher wages, entertainment and tourism facilities available. Fasilitas sarana dan prasarana yang terbatas, kurangnya lapangan pekerjaan di Desa Lebo menyebabkan penduduk mobilitas ke daerah lain. Tujuan penelitian ini untuk mengetahui Faktor-faktor yang menyebabkan penduduk melakukan mobilitas. Penelitian ini menggunakan pendekatan kuantitatif. Populasi penelitian ini semua KK di Desa Lebo yang berjumlah 1209 KK. Metode pengambilan sampel menggunakan Propotionate Area Random Sampling sebesar 10% dari populasi dan dihasilkan 120 KK. Teknik pengambilan data yang digunakan yaitu angket, observasi dan dokumentasi. Teknik analisis data menggunakan deskriptif presentase (DP). Variabel penelitian ini yaitu faktor pendorong dan penarik yang menyebabkan penduduk melakukan mobilitas. Hasil penelitian ini menunjukkan faktor dari Desa Lebo seperti kurangnya sarana dan prasarana, lapangan pekerjaan, upah pekerjaan rendah yang menyebabkan penduduk melakukan mobilitas ke daerah lain. Faktor penarik dari daerah lain seperti sarana dan prasarana lebih lengkap, lapangan pekerjaan banyak, upah pekerjaan lebih tinggi,tersedia tempat hiburan dan wisata.